Enhancing 11th-Grade Letter Writing Through ChatGPT-Based Free Writing - Bedrio, Muhammad Juliansyah; Prasodjo, Pandu; Priambada Purba, Hilarius Raditya (Journal of English Language and Education, 2025)
This quantitative study investigated the impact of ChatGPT-assisted free writing on idea development in letter writing among seven 11th-grade students at SMA NAM IBS over six weeks. Using a single-group pre-test-post-test design, five assessments were conducted: a pre-test, three ChatGPT-assisted exercises, and a post-test. Descriptive statistics showed an increase in mean scores from pre-test (M = 78.43) to post-test (M = 86.00), indicating improvement. However, repeated measures ANOVA showed no significant difference (F(4, 24) = 1.43, p 0.05). This may have been due to small sample size, non-normal data, sphericity violations, and high within-subject variability. Despite the lack of statistical significance, the upward trend suggested potential benefits of ChatGPT. Further research with larger samples, improved rubrics, and adjusted statistical methods was suggested to validate ChatGPT’s effectiveness in enhancing idea development.Keywords: ChatGPT, Free Writing, Idea Development, Letter Writing